2013
DOI: 10.1016/j.combustflame.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

On the phase between pressure and heat release fluctuations for propane/hydrogen flames and its role in mode transitions

Abstract: This paper presents an experimental investigation into mode-transitions observed in a 50-kW, atmospheric pressure, backward-facing step combustor burning lean premixed C 3 H 8 /H 2 fuel mixtures over a range of equivalence ratios, fuel compositions and preheat temperatures.The combustor exhibits distinct acoustic response and dynamic flame shape (collectively referred to as "dynamic modes") depending on the operating conditions. We simultaneously measure the dynamic pressure and flame chemiluminescence to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 38 publications
7
22
0
Order By: Relevance
“…2. These limits are consistent 2 The pressure amplitude is low as compared to the case of a longer combustor presented in [14,16]. 3 The mechanism of the instability is discussed in our prior studies [14,16].…”
Section: Operating Regimessupporting
confidence: 67%
See 2 more Smart Citations
“…2. These limits are consistent 2 The pressure amplitude is low as compared to the case of a longer combustor presented in [14,16]. 3 The mechanism of the instability is discussed in our prior studies [14,16].…”
Section: Operating Regimessupporting
confidence: 67%
“…Our prior studies [14,16] demonstrated that the strained consumption speed can be used to collapse the scatter of the mode-transitions observed over a range of mixture compositions and inlet temperatures. In this section, we attempt to correlate the reattachment length with the consumption speed.…”
Section: Correlating the Reattachment Length With The Flame Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the cause of the η p variations, we show in figure 7(c,d) the Rayleigh index: RI ≡ 1/T T 0 p (t)q (t) dt, where T is the sampling duration (Lieuwen & Yang 2005). This is used to quantify the magnitude and direction of the energy exchange between the flame and the acoustic modes, accounting not only for the amplitude variations in p (t) and q (t) but also for their phase relationship (Hong et al 2013). The Rayleigh indices of the three main modes (RI * 1 , RI * 2 , RI * f ) are computed by bandpass filtering (±5 Hz) the p (t) and q (t) signals with a zero phase-distortion algorithm based on a forward-backward scheme (Gustafsson 1996).…”
Section: Asynchronous Quenching and Resonant Amplificationmentioning
confidence: 99%
“…3, we observe two distinct unstable regimes in which the combustor oscillates at two different frequencies, e.g., ∼40 Hz and ∼70 Hz, which are referred to as low-frequency unstable regime and high-frequency unstable regime, respectively. 3 According to the one dimensional acoustic analysis (Hong et al, 2013a), the low-frequency unstable regime (∼40 Hz)…”
Section: Stability Characteristicsmentioning
confidence: 99%